The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1155/2013/821745
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Efficiencies of Michigan Neuropathy Screening Instrument, Neurothesiometer, and Electromyography for Diagnosis of Diabetic Neuropathy

Abstract: Aim. This study compares the effectiveness of Michigan Neuropathy Screening Instrument (MNSI), neurothesiometer, and electromyography (EMG) in detecting diabetic peripheral neuropathy in patients with diabetes type 2. Materials and Methods. 106 patients with diabetes type 2 treated at the outpatient clinic of Ankara Numune Education and Research Hospital Department of Endocrinology between September 2008 and May 2009 were included in this study. Patients were evaluated by glycemic regulation tests, MNSI (quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 16 publications
4
25
0
3
Order By: Relevance
“…The Brazilian raters affirmed that the MNSI is a simple, fast and easy-to-apply test performing it in around three minutes. The Brazilian experience confirme the point of view from the specialists who used the original version of the MNSI 9,19,20 . We tested the MNSI-Brazil in a sample composed by patients who schooling at least 7 years and were able to read and write well.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The Brazilian raters affirmed that the MNSI is a simple, fast and easy-to-apply test performing it in around three minutes. The Brazilian experience confirme the point of view from the specialists who used the original version of the MNSI 9,19,20 . We tested the MNSI-Brazil in a sample composed by patients who schooling at least 7 years and were able to read and write well.…”
Section: Discussionsupporting
confidence: 65%
“…Although electrophysiological studies be the best option to diagnose DSPN, they are expensive and, for this reason, must not be the initial tool to screening; nerve conduction studies must be recommended after the clinical approach, by which the MSNI-Brazil can provide additional information to the therapeutical decision-taking 9,10,11,19 . The MNSI-Brazil reveals that our sample presented few signals to conclude a neuropathy diagnosis as observed in our results showing just two subjects scored near from the minimum to be considered a suggestion of DSPN.…”
Section: Discussionmentioning
confidence: 99%
“…One limitation of our study was the fact that the instrument was used only for a sample of patients from just one hospital, albeit a major hospital, with a reference population of 2 million inhabitants. The authors believe that the same results would be found in different areas of the country, as the original instrument was developed by the Neurology Department of Michigan University, using a sample of 56 patients with diabetes, and the NCS was the gold standard in order to confirm the diagnosis and to grade neuropathy …”
Section: Discussionmentioning
confidence: 76%
“…Vibration perception at great toe was then evaluated; vibration is scored as 0 point, 0.5 point and 1 point respectively if the vibration sense was present, decreased or absent. The total score was the sum of the score of each item for both feet; a score >2.5 was considered abnormal …”
Section: Methodsmentioning
confidence: 99%
“…The total score was the sum of the score of each item for both feet; a score >2.5 was considered abnormal. 20 Exercise self-efficacy was measured using the self-efficacy for exercise scale. The scale was developed by Bandura and has shown great reliability and validity; the internal consistency of the scale was considered satisfactory (Cronbach's alpha = 0.937).…”
Section: Individual Characteristicsmentioning
confidence: 99%